Social enterprises and their ecosystems in Europe (Publications Office of the European Union, 2016)
The analyses conducted in this study have revealed that 20 784 social enterprises existed in Poland in 2014. At this time, social enterprises employed 265 801 individuals, but their employment potential, measured in the full-time equivalent (FTE), was estimated at 103 201 workers. As far as types of social enterprises are concerned, the most numerous are entrepreneurial non-profit organisations, estimated at 19 400. They are followed by 1 269 social cooperatives, 88 ZAZ and only 27 non-profit companies. The total number of WISEs is estimated at 1 357 entities.
10.2767/561410
Keywords: Amtsdruckschrift; Graue Literatur; Sozialwirtschaft; Polen; social policy; social economy; social impact; European undertaking; financial aid; entrepreneurship; investment; cartography; non-profit organisation; Poland; report